2008
DOI: 10.1177/0261927x07313652
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Discrimination in Minimal Groups

Abstract: In line with recent evidence of linguistic discrimination within minimal groups, the present experiment examines the effects of asymmetries of status between minimal groups on linguistic discrimination. Equal-, high-, and low-status groups were created by modifying the standard minimal group condition. Linguistic data were obtained by asking participants to describe a choice (parity vs. in-group favoritism vs. out-group favoritism) made by either an in-group or an out-group member in allocating negative outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 28 publications
7
27
2
Order By: Relevance
“…This observation is in line with research showing that ingroup deviants are more disparaged than outgroup deviants when ingroup superiority is undermined (e.g., Marques et al, 2001). Studies have shown that use of the different aspects of the LIB pattern (e.g., for ingroup behaviors vs. outgroup behaviors) may vary according to the aspects of the intergroup context (Maass et al, 1996;Moscatelli, Albarello, & Rubini, 2008). Our results suggest that the normativity of the LIB is also highly context sensitive and may vary with respect to the nature of the intergroup relations.…”
Section: Discussionsupporting
confidence: 89%
“…This observation is in line with research showing that ingroup deviants are more disparaged than outgroup deviants when ingroup superiority is undermined (e.g., Marques et al, 2001). Studies have shown that use of the different aspects of the LIB pattern (e.g., for ingroup behaviors vs. outgroup behaviors) may vary according to the aspects of the intergroup context (Maass et al, 1996;Moscatelli, Albarello, & Rubini, 2008). Our results suggest that the normativity of the LIB is also highly context sensitive and may vary with respect to the nature of the intergroup relations.…”
Section: Discussionsupporting
confidence: 89%
“…In Study 2, competence turned out to work as the main predictor of ingroup identification when respondents compared to Romanians, underlining that competence is a more useful dimension of positive comparison than sociability when the outgroup has a lower status. This result is in line with the importance generally assigned to social status and competence in intergroup comparison (Fiske et al, ; Moscatelli, Albarello, & Rubini, ; Tajfel & Turner, ).…”
Section: Studysupporting
confidence: 87%
“…The results of Study 1 prove evidence on linguistic intergroup discrimination under stereotypic categorizations of in-group and out-group members (Maass, 1999;Maass et al, 1989;Moscatelli et al, 2008Moscatelli et al, , 2014Moscatelli & Rubini, 2011;Wigboldus & Douglas, 2007) and demonstrated for the first time that this tendency disappeared when participants encountered counterstereotypic information on in-group and out-group targets. In other words, the abstraction of positive and negative terms used to describe the target did not vary between the Italian in-group and the Romanian out-group.…”
Section: Two Cognitive Interventions Hindering Linguistic Out-group Dsupporting
confidence: 57%
“…In the stereotypic combination condition, we expected to obtain findings in line with the literature on linguistic intergroup discrimination (e.g., Moscatelli et al, 2008). Participants would describe the stereotypic out-group target using negative terms at a higher abstraction and positive terms at a lower abstraction than the stereotypic in-group target.…”
Section: Studymentioning
confidence: 76%